OER AWARENESS AND USAGE AMONG OPEN AND DISTANCE LEARNING STUDENTS IN SOUTH-WESTERN NIGERIA - Sunday Abidemi Itasanmi (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This study assessed Open Educational Resources (OER) awareness level and usage among Open and Distance Learning (ODL) students in South-western Nigeria. A descriptive research design was adopted for the study. Three ODL institutions (University of Ibadan Distance Learning Centre, National Open University of Nigeria, Ibadan Study centre and University of Lagos Distance Learning Institute) were purposively selected. A structured questionnaire titled "OER awareness and usage Questionnaire" with Cronbach alpha coefficient of .954 was used as data collection instrument. Data collected were analysed using frequency count, simple percentages, mean, standard deviation and Pearson Product Moment Correlation. Results of the study revealed that OER awareness among ODL students was on the average while OER usage was high. Lack of orientation on the availability and use of OER and insufficient ICT facilities in the school to access OER materials, amongst others were challenges ODL students faced using OER. It was, therefore, recommended that there should be conscious efforts by ODL institutions to devise means to increase the level of OER awareness among students and sensitise them on the inherent benefits in OER usage.